2012
DOI: 10.1002/cae.20439
|View full text |Cite
|
Sign up to set email alerts
|

An educational tool for wireless sensor networks

Abstract: ABSTRACT:The present paper introduces a tool, which simplifies the description of Wireless Sensor Networks (WSN) applications by means of a visual language and automatic generation of executable code. The tool has been used to provide non-experienced students with a practical introduction to WSN concepts in a short period of time. Using the tool allowed students to quickly develop their own applications and test with them, focusing on their functional aspects rather than on programming and platform-dependent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Zhong et al showed the implementation of a platform for teaching, analysis, and construction of “Mesh” wireless networks. Research by introduces a tool, which simplifies the description of wireless sensor networks applications by means of a visual language and automatic generation of executable code.…”
Section: Learning Through the Action: A Brief Reviewmentioning
confidence: 99%
“…Zhong et al showed the implementation of a platform for teaching, analysis, and construction of “Mesh” wireless networks. Research by introduces a tool, which simplifies the description of wireless sensor networks applications by means of a visual language and automatic generation of executable code.…”
Section: Learning Through the Action: A Brief Reviewmentioning
confidence: 99%
“…They improve the theoretical knowledge, hand skills, and problem‐solving skills in real time Wi‐Fi systems. There are many proposed educational tools for digital and wireless communication topics using different techniques and platforms such as a Web‐based, LabVIEW, MATLAB, universal software radio peripheral (USRP), and field programmable gate array (FPGA) in the literature . Bayilmis designed and implemented a web‐based educational tool based on MATLAB for engineering students in remote laboratories .…”
Section: Introductionmentioning
confidence: 99%
“…The most relevant Universities in different countries have included, in their engineering studies, this kind of subjects . Most of these courses are oriented to provide the student with technical knowledge about the radio access networks, from a theoretical point of view, with theoretical lectures, and some of them with a practical work, by means of systems simulations for a specific and close environment . However, very few of them try to provide a global view of the mobile network, showing the student the economical implications of the technological decisions, but the impact of economic issues is achieving a growing relevance and deserves to be considered .…”
Section: Introductionmentioning
confidence: 99%